Kinerja Aerasi Venturi Dalam Meningkatkan Kualitas Air - Kusuma, Brillyan; Nurul Hidayah, Euis; Hendriyanto Cahyonugroho, Okik (Jurnal Serambi Engineering, 2024)
Effective and efficient water treatment is needed to improve water quality. The content of iron (Fe) and manganese (Mn) compounds in water is a major problem that can affect health and interfere with human activities. One of the steps that can be taken to degrade manganese is oxidation using aeration. In this study, variations in the diameter of venturi aerators were used to determine the performance of venturi aeration in water treatment. The variation in diameter was set at 12mm, 10mm and 8mm sizes. Based on the results of the study, dissolved oxygen levels have increased over time. The highest increase in dissolved oxygen content was achieved with the 12 mm diameter variation with dissolved oxygen levels reaching 7.8 mg/litre within 60 minutes. a significant reduction in iron content of 92% with an iron content of less than 0.0567 mg/litre. The largest percentage decrease in manganese content occurred with the variation of the aerator vent hole diameter of 12 mm, which was 54% with an aeration time of 15 minutes. There is a fluctuation in the decrease in manganese content caused by the more difficult to oxidise properties of manganese.